Immune-related adverse events of immune checkpoint inhibitors: a review - Yin, Qinan; Wu, Liuyun; Han, Lizhu; Zheng, Xingyue; Tong, Rongsheng; Li, Lian; Bai, Lan; Bian, Yuan (Frontiers in Immunology, 2023)
Since the first Immune Checkpoint Inhibitor came out in 2011, tumor immunotherapy has entered a new era, and the response rate and survival rate of many cancers have also been improved. Despite the success of Immune Checkpoint Inhibitors, resistance to these drugs limits the number of patients who can achieve a lasting response, and immune-related adverse events complicate treatment. The mechanism of irAEs is not clear. We discuss the mechanisms of action of immune checkpoint inhibitors, the different types of immune-related adverse events and their possible mechanisms, and describe possible strategies and targets for prevention and therapeutic interventions to mitigate them.